American cocktail : a "colored girl" in the world - Reynolds, Anita Thompson Dickinson, 1901-1980 (Harvard University Press, 2014)
Of racially mixed heritage, Anita Reynolds was proudly African American but often passed for Indian, Mexican, or Creole. Actress, dancer, model, but above all free-spirited provocateur, she was, as her Parisian friends nicknamed her, an "American cocktail."In prose that perfectly captures the globetrotting nonchalance of its author, American Cocktail presents a stimulating, unforgettable self-portrait of a truly extraordinary woman